Economic empowerment of free trade zone identity labels: the impact of multi-dimensional identity labels on consumer purchase intention for organic food - Zhang, Yan (Frontiers in Nutrition, 2026)
Extensive prior research has confirmed that label information on food packaging is a crucial factor in stimulating consumer purchase intention, such as labels indicating sugar content, fat content, and purine content. However, few studies have focused on the impact of multi-dimensional geographical identity labels for organic food on consumer purchase intention. This study takes the geographical identity of organic food using free trade zones and provincial administrative regions as examples, treating them as dual identities of organic food production areas. We recruited 848 participants and conducted three online scenario-based experiments to verify the impact of multi-dimensional (vs. single) identity labels of organic food production areas on consumer purchase intention. The results show that compared to single identity labels, multi-dimensional identity labels of organic food production areas can effectively enhance consumer purchase intention. Among these, the regional identity triggered by multi-dimensional identity labels becomes an important factor in boosting consumer purchase intention. However, consumer regional attitudes can effectively moderate the relationship between multi-dimensional identity labels and consumer purchase intention. This study is the first to verify the positive role of multi-dimensional identity labels of organic food production areas in the field of organic food consumption, providing valuable measures for the marketing of organic food in free trade zones. While these findings are derived from the context of Chinese free trade zones and may be influenced by cultural and economic specificities, they offer a foundation for future cross-cultural validations in global organic food markets.